Illumination of Hanjuang Flower Patterns in Mushaf Qur'an Sundawi - Agus Malik Ibrahim; Rahma Wahdiniwaty (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research is motivated by the illumination of the Hanjuang floral motif in theSundawi Qur'anic manuscript. Meanwhile, in general, manuscripts that are often circulated in goodprint from middle eastern Indonesia use illumination with a geometric Islamic pattern. Thepurpose of this study is to explain the Sundawi Qur'an as a whole related to the formulation of theHanjuang floral motif illumination concept, an explanation of the Hanjuang floral motifillumination, and the relevance of the Hanjuang floral motif illumination to the Sundawi Qur'anicMushaf. This study uses a qualitative method with an aesthetic approach that systematicallydescribes the things that are the focus of the research. The data collection technique used in thisresearch is library research and field research using the interview method with informants. Theresults of this study found that the formulation of the concept of illumination of the Hanjuangfloral motif with the Sundawi Qur'anic Mushaf is one of the characteristics of West Java plants orflora and also as a means of introducing West Javanese ornaments in Sundawi Qur'anicmanuscripts, this illumination will have an impact on the synergy between the decorative motifsand the writings on the Sundawi Qur'anic manuscripts verse and the Hanjuang motifs affect thereader's enthusiasm to continue reading the Qur'an